A construção social do currículo nas reformas do curso delicenciatura em ciências biológicas da Universidade Federal deAlfenas (UNIFAL-MG) - Gabriel Menezes Viana (2010)
This research has its central objective to analyze the main factors responsible for changes in the curriculum of a Teacher Training Course in Science and Biology led by Federal University of Alfenas. Based on Ivor Goodsons idea of curriculum as a social construction, this study focus on the relationship among people directly involved in the organization of the curriculum trying to understand how their interest and conceptions influenced this process of changes. Thomas Popkewitz study on reform was also important because it allows to understand curriculum reform as an ecologic phenomenal, in other words his work shows howimportant is the context outside the school in the process of curriculum change. The methodological approach is the case studies where was used documents and semi-structured interviews to collect the data. In conclusion the study points that the main factors which influenced the construction of the curriculum were: the transformation undergone by theinstitution as well by the Brazilian political and educational context in the last two decades; the interest of the agents directly involved in the reform process; the discourses about the Brazilian teacher training courses curriculum guidelines and the state regulation on the profession on biologist.